A transversalidade no currículo do ensino fundamental: as questões ambientais em foco - Aquino, Maria Sacramento (2008)
This thesis is the result of an investigation about the transversality of the environmental issues into the daily curriculum of High Schools (from first to eighth grade). The research field was the county of Santo Antonio de Jesus in the state of Bahia, Brazil. The investigation is related with the challenge that the present model of social development and organization has put to the school institution: to bring the regular discussion about Environmental Education (EE) to the school s daily life. Facing the complexity of the socio-environmental issues and the basic functions of Education, the object of study was restricted to the identification of the challenges and paradoxes of the EE inside the curriculum organization of Politic-Pedagogic Project of the schools and the teachers daily practices. About the methodology, we adopted different references for the qualitative research: sociology, history, economy, and education. As for the investigative procedures about the teacher s practices, we related the school s daily practices to the context of the community. We also adopted several investigative procedures, such as questionnaires, interviews, observations and formative intervention. The theoretical basis was organized based on references to curriculum organization, environmental culture, teacher education and also considering the pillars of a capitalistic system that is based on consumerism and that generates social exclusion. At the initial considerations, we contextualized the contemporary environmental issues in an attempt to interpret the conditions of the EE transversality into the school s daily practices, which are still oriented to the traditional Cartesian Education. Based on the collected data, we found the reasons for the teachers dilemma and reluctances to the insertion of the environmental issues into the organization of the work plan and into the management of a school. Nevertheless, the results also signed promising possibilities to the EE tranversality, in case the curriculum of the school could be more sensible towards the cultural and social-economical issues of a community. We especially questioned The National Curriculum Parameter s (PCN), which is considered highly insufficient to inform the teachers about the environmental issues, facing the actual local conditions of social and pedagogic work. The final considerations showed the role and the importance of this research as one strategy to organize the curriculum education into the perspective of the transversality of environmental issues inside the education of both teacher and student